Saliva testing for human papilloma virus in oropharyngeal squamous cell carcinoma: A diagnostic accuracy study. (10th July 2017) - Qureishi, A.; Ali, M.; Fraser, L.; Shah, K.A.; Møller, H.; Winter, S.
Abstract : Background: New cases of oropharyngeal squamous cell carcinoma (OPSCC) are routinely tested for HPV. HPV in saliva can be detected with PCR, but its clinical applicability in the context of OPSCC remains unknown. Methods: Forty‐six consecutive patients diagnosed with OPSCC had pre‐treatment saliva specimens collected. PCR for HPV on saliva was compared to p16 IHC and HPV DNA in situ hybridisation (ISH) on surgical biopsies. Results: The sensitivity and specificity of saliva testing when compared to the reference test of p16 IHC and HPV DNA ISH were 72.2% and 90%, and positive and negative predictive values were 96.3% and 47.4%. There were no adverse events. Time from last meal, smoking, alcohol drinking and physical exercise did not impact on results. Conclusions: Saliva testing is a promising test to detect HPV in patients with OPSCC. A positive result could avoid the need for surgical biopsies, thereby reducing costs, patient morbidity and expedite treatment.